STUDI SIFAT FISIS DAN MEKANIS SOLIDIFIKASI BESI COR KELABU PADA CETAKAN PERMANEN UNTUK TAPPING AWAL - Widagdo, Jati; , Agus yulianto, ST.MT (2016)
ABTRACTION This study aims to determine the effect of the carbon coating on the solidification of gray cast iron in a permanent mold for the initial tapping. This study uses a permanent mold cast iron ductile (FCD). The research methodology was conducted with cast iron melting in induction furnace and then is poured in the mold FCD were coated carbon to create gray cast iron specimen then test the physical properties and mechanical. Tests in liquid form gray cast iron using test equipment CE Meter and the gray cast iron specimen in chemical composition with spectrometer later in the micro hardness tester and photos are taken from the direct contact with the air and direct contact with the mold FCD. Results of the research is a chart obtained from CE Meter shows the temperature of 1332.5 ° C during tapping early in the cast in the mold at the start on the chart that reads CE Meter decrease temperature, the temperature of liquid 1165 ° C shape is still liquid to a temperature of solid 1112.3 ° C so that obtained value CEL = 4.08%; C = 3.5%; and SI = 2.3% where the metal solid starts but is still red up to a temperature of 1060 ° C and hardened within 180 seconds, while the results of chemical composition in the form of solid or solid among others: Fe 93.25%; C 3.69%; 1.94% Si and other elements under 1%. The test results microstructure upper direct contact with the air contained in the form lamellar graphite while the direct contact with the mold FCD looks cementite and results of hardness test specimens were coated carbon amounted to 163.05 kg / mm². Based on these data we can conclude that in the permanent mold in the coated carbon speeds the clotting at the direct contact with the mold to form clots FCD white. Keywords: olidification, molding FCD, spectrometer, microstructure, hardness.